The effectiveness of web-based Schoology learning media on informatics learning outcomes of grade VIII students at UPT SMP Negeri 4 Baranti, Sidenreng Rappang Regency - Nur Azima Nur Azima; Hasanuddin Bambeng; Syamsunir Syamsunir (Edumaspul: Jurnal Pendidikan, 2025)
The Effectiveness of Web-Based Schoology Learning Media on Informatics Learning Outcomes of Class VIII Students of UPT SMP Negeri 4 Baranti, Sidenreng Rappang Regency”. Supervised by Syamsunir and Hasanuddin. This study aims to determine the effectiveness of web-based Schoology learning media on Informatics learning outcomes of class VIII students of UPT SMP Negeri 4 Baranti, Sidenreng Rappang Regency. The research method used is quantitative with a deductive approach. This type of research is quasi-experimental with a one-group pretest and posttest design. This study does not use a control group, but rather compares student learning outcomes before and after using Schoology learning media. Data were collected through pretest and posttest tests. The results showed an increase in student scores after using Schoology learning media. The highest pretest score was 66 and the lowest score was 30, while in the posttest the score increased to 96 and the lowest score was 70 so the average score Mx (Posttest) = 82.64 > My (Pretest) = 49.05. This indicates an increase in learning outcomes after using the Schoology learning media. Therefore, it can be concluded that the web-based Schoology learning media used in Informatics demonstrates effective student learning outcomes.